The Future Role of Renewables in Turkey’s Electricity Supply Security - Uyanık, Sırrı (International Journal of Energy Economics and Policy, 2018)
As a fast-developing economy, Turkey’s energy needs have also been growing rapidly for several decades. Its indigenous resources have been evaluated as insufficient to meet this rapidly increasing demand for energy, especially power. Therefore, it imports around half of its energy needs for power. Recently, it has newly started tapping into renewable sources, especially wind and solar. Considering these developments and official aims, this paper attempts to answer the question of which role this renewable developments can play in providing electricity supply security, which is a critical part of energy security. Whereas it seems clear that Renewables will certainly grow, whether this growth makes a significant difference from a reliability perspective is questionable. In other words, due to the problem of the intermittency, the requirement to provide backup power from thermal capacity seems obvious under today’s technological conditions. Therefore, the official policy needs urgently to consider and encourage investments in technological solutions (especially energy storage). Keywords: Renewable Energy, Energy Security, Reliable Power Supply JEL Classifications: Q21, K32